Analysis of Total Reducing Sugar Content, Acidity Value, and Hydroxymethylfurfural (HMF) Content of Various Honey Types - Agrib Nur Ayubi (Universitas Negeri Yogyakarta, 2018)
The aims of this research are to determine the total reducing sugar content, acidity value, and hydroxymethylfurfural (HMF) content of various honey types in Special Region of Yogyakarta and Central Java. Those types sample of honey are sengon, randu, kelengkeng, rambutan, and kopi honey from several places in Yogyakarta and Central Java. This research using analytical method, there are iodometry titration, acid-base titration, and UV-Vis spectrophotometry. The result of total reducing sugar content from sengon honey 74.40%, randu honey 61.42%, kelengkeng honey 62.07%, rambutan honey 88.14%, and kopi honey 87.04%. Acidity value of sengon honey 71.33 mL/Kg, randu honey 116.67 mL/Kg, kelengkeng honey 41.33 mL/Kg, rambutan honey 32.00 mL/Kg, and kopi honey 70.00 mL/Kg. HMF content of sengon honey 14.7 mg/Kg, randu honey 39.7 mg/Kg, kelengkeng honey 45.2 mg/Kg, rambutan honey 47.5 mg/Kg, and kopi honey 38.8 mg/Kg. In spite of the result of this analysis is more than the number of Indonesian National Standard of honey, those honeys are still good and doesn’t mean there are forbidden to consume it.